1996
DOI: 10.1159/000177132
|View full text |Cite
|
Sign up to set email alerts
|

Left-Ventricular Hypertrophy in the Elderly: Unreliability of ECG Criteria in 477 Subjects Aged 65 Years or More

Abstract: Aim: To evaluate the diagnostic reliability of the ECG diagnosis of left-ventricular hypertrophy (LVH) in a cohort of elderly subjects taken from a general population. Patients: The 447 subjects with perfect echocardiography and ECG results of the 2,254 included in the Cardiovascular Study in the Elderly. Methods: Sensitivity, specificity, positive and negative predictive value of the most commonly used ECG tests of LVH were calculated versus the gold standard, echocardiography. Results: All ECG tests had a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
0
13
1
Order By: Relevance
“…34 In the present study, however, LVH defined by ECG was not significantly different between subjects with and without MBs. As several studies have reported ECG-defined LVH is not reliable, 35,36 which may explain the failure of the association between LVH and MBs in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…34 In the present study, however, LVH defined by ECG was not significantly different between subjects with and without MBs. As several studies have reported ECG-defined LVH is not reliable, 35,36 which may explain the failure of the association between LVH and MBs in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Although the hypertensive patients in our study were slightly older than those in corresponding clinical studies, age does not seem to explain the difference in prevalence rates of LVH. [16][17][18]28 It seems more likely that the duration of hypertension and blood pressure levels, in our study, play more important roles in explaining the prevalence of LVH. Most of our LVH patients (62%) had had hypertension for more than 10 years whereas the figure for non-LVH patients was 48%.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that electrocardiographic and echocardiographic left ventricular hypertrophy reflect two different approaches. The former depends on the electric activity of myocardial fibres (which increase with the pressor load), the latter on the myocardial mass (which can simply increase with growing old due to an accumulation of electrically-inactive connective tissue 58 ). Consequently, in the elderly heart weight detected with echocardiogram has a prognostic value related to that of age, and it is not surprising that it does not predict mortality after correction for age.…”
Section: Discussionmentioning
confidence: 99%